FRAGMENTS OF OCEANIC ISLANDS IN ACCRETION-COLLISION AREAS OF GORNY ALTAI AND SALAIR, SOUTHERN SIBERIA, RUSSIA: EARLY STAGES OF CONTINENTAL CRUSTAL GROWTH OF THE SIBERIAN CONTINENT IN VENDIAN-EARLY CAMBRIAN TIME - Dobretsov N.L.; Buslov M.M.; Yu U. (My University, 2004)
The Altai-Salair area in southern Siberia is a Caledonian folded area containing fragments of Vendian–Early Cambrian island arcs. In the Vendian–Early Cambrian, an extended system of island arcs existed near the Paleo-Asian Ocean/Siberian continent boundary and was located in an open ocean realm. In the present-day structural pattern of southern Siberia, the fragments of Vendian–Early Cambrian ophiolites, island arcs and paleo-oceanic islands occur in the accretion–collision zones. We recognized that the accretion–collision zones were mainly composed of the rock units, which were formed within an island-arc system or were incorporated in it during the subduction of the Paleo-Asian Ocean under the island arc or the Siberian continent. This system consists of accretionary wedge, fore-arc basin, primitive island arc and normal island arc. The accretionary wedges contain the oceanic island fragments which consist of OIB basalts and siliceous—carbonate cover including top and slope facies sediments. Oceanic islands submerged into the subduction zone and, later were incorporated into an accretionary wedge. Collision of oceanic islands and island arcs in subduction zones resulted in reverse currents in the accretionary wedge and exhumation of high-pressure rocks. Our studies of the Gorny Altai and Salair accretionary wedges showed that the remnants of oceanic crust are mainly oceanic islands and ophiolites. Therefore, it is important to recognize paleo-islands in folded areas. The study of paleo- islands is important for understanding the evolution of accretionary wedges and exhumation of subducted high-pressure rocks.
Keywords: Ophiolites; Paleo-oceanic; Fragments; Cambrian; Vendian; Paleozoic::Cambrian; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская::Вендский; Precambrian::Proterozoic::Neoproterozoic::Vendian